2012
DOI: 10.1373/clinchem.2012.187914
|View full text |Cite
|
Sign up to set email alerts
|

ELISA System for Human Endothelial Lipase

Abstract: BACKGROUND Endothelial lipase (EL) regulates the metabolism of HDL cholesterol (HDL-C). However, the role of EL in regulating plasma HDL-C concentrations and EL's potential involvement in atherosclerosis in humans has not been fully investigated due to the lack of reliable assays for EL mass. We developed an ELISA system for serum EL mass. METHODS Human recombinant EL proteins, purified from cultured media of human EL–transfe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
3
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 18 publications
(33 citation statements)
references
References 43 publications
3
24
3
3
Order By: Relevance
“…Although previous studies showed that pre- and post-heparin EL plasma levels are highly correlated 8 or similar 34 , the possibility cannot be excluded that post-heparin EL plasma levels would be differently affected by AHF-associated pathophysiological conditions and MetS compared to our findings with pre-heparin EL plasma levels. Furthermore, considering EL polymorphisms associated with decreased EL enzyme activity 15, 16 , together with possibly altered plasma levels of EL inhibitors, such as angiopoetin-like protein 3 35 or protein convertases 36 in AHF, the association of EL activity with plasma lipids/lipoproteins 9 might be different from what was found for the EL mass in this study.…”
Section: Discussioncontrasting
confidence: 85%
“…Although previous studies showed that pre- and post-heparin EL plasma levels are highly correlated 8 or similar 34 , the possibility cannot be excluded that post-heparin EL plasma levels would be differently affected by AHF-associated pathophysiological conditions and MetS compared to our findings with pre-heparin EL plasma levels. Furthermore, considering EL polymorphisms associated with decreased EL enzyme activity 15, 16 , together with possibly altered plasma levels of EL inhibitors, such as angiopoetin-like protein 3 35 or protein convertases 36 in AHF, the association of EL activity with plasma lipids/lipoproteins 9 might be different from what was found for the EL mass in this study.…”
Section: Discussioncontrasting
confidence: 85%
“…1D). Moreover, we recently reported that the plasma EL mass is similar between pre-and post-heparin plasma samples 12) . Therefore, the effects and dose-dependency of heparin treatment on the plasma EL mass and activity must be determined in detail in further studies.…”
Section: Notementioning
confidence: 81%
“…EL-IP was performed using a monoclonal IgG antibody against human full-length EL proteins raised in mice (clone 26A1, Immuno-Biological Laboratories, Fujioka, Gunma, Japan) that reacts with the amino terminus of EL proteins 12) . 26A1 mouse IgG (10 μL, 1 μg) was crosslinked onto 40 μL of nProtein A and incubated overnight with the 300-μL conditioned plasma samples to immunoprecipitate EL.…”
Section: Plasma Igg Removal and Immunoprecipitationmentioning
confidence: 99%
See 2 more Smart Citations